STUDI KARAKTERISTIK PROSES GASIFIKASI BERBAGAI JENIS BIOMASSA PADA GASIFIER DOWNDRAFT - , AGUS AKTAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Biomass gasification is an endothermic reaction process for converting biomass into syngas, occurs at high temperatures with limited oxygen. Knowing the temperature profile of biomass gasification wood charcoal, coconut shell charcoal and coconut shell, rice husk and woodchip and seek optimal results from gasification of biomass are the purpose of the research. The equipment in this research consisted of